The plan - Paul, Alison; Lehman, Barbara (New York : Houghton Mifflin Harcourt, 2015)
Coping with a loss, a father and daughter rediscover an important piece of family history and begin to build a new life filled with adventure, in a book that features twenty letter-by-letter word shifts.
"A Junior Library Guild selection"--Jacket flap.
Elementary Grade.
Keywords: Fathers and daughters -- Juvenile fiction; Families -- Juvenile fiction; Fathers and daughters -- Fiction; Imagination -- Fiction; Bereavement -- Fiction